Analysis Of Financial Performance at Property, Real Estate, And Building Construction Sector Company That Listed On The Indonesia Stock Exchange - Rahmaliana, Aghnia; Shalsadilla, Tiara Fitriani; Setiawan, Giantry Rizky Wulandari; Riyanthi, Ayu Putri (SINTESA, 2024)
Financial performance is an analysis or evaluation of the achievements, accomplishments or financial results of a company in a certain period. This includes the company's ability to create value for shareholders in an effective and efficient manner, as well as comparing actual performance with what it should be. This research aims to determine and analyze performance property, real estate and building construction sector finance based on financial ratio analysis (profitability ratio, liquidity ratio and leverage ratio). This type of research is descriptive qualitative research. Data obtained from companies is identified and analyzed using financial ratio analysis. The results of the research and discussion can be concluded that if we look at the profitability ratio of PT Puradelta Lestari Tbk is the best, the liquidity ratio of PT Jaya Real Property Tbk is the best, and the leverage ratio of PT Metropolitan Land Tbk is the best. This conclusion is drawn from the average comparison. the entire period.